Land Resources Inventory In Developing Countries : A Problem of Collecting and Generating Relevant Data A Typical Case of Atmospheric Water Balance Inventory. - Tejoyuwono Notohadiprawiro (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 1986)
-